Efficacy and safety of ombitasvir/paritaprevir/ritonavir combination therapy for genotype 1b chronic hepatitis C patients complicated with chronic kidney disease. Issue 7 (21st February 2018) - Arai, Taeang; Atsukawa, Masanori; Tsubota, Akihito; Ikegami, Tadashi; Shimada, Noritomo; Kato, Keizo; Abe, Hiroshi; Okubo, Tomomi; Itokawa, Norio; Kondo, Chisa; Mikami, Shigeru; Asano, Toru; et al.
Abstract : Aim: The aim of this study was to clarify the effects and safety of ombitasvir/paritaprevir/ritonavir (OBT/PTV/r) therapy in genotype 1b chronic hepatitis C patients with non‐dialysis chronic kidney disease (CKD). Methods: This retrospective, multicenter study of 12‐week OBT/PTV/r therapy included genotype 1b patients with non‐dialysis CKD. Chronic kidney disease was defined as an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 . Virologic responses and treatment‐emergent adverse events (TEAEs) in patients with CKD were compared with those in patients without CKD. Results: Two hundred and thirty‐five patients with a median age of 67 years (range, 27–89 years) were enrolled, consisting of 181 patients without CKD and 54 patients with CKD. Overall, the rates of rapid virologic response (RVR), end of treatment response (ETR), and sustained virologic response (SVR) were 78.7%, 98.7%, and 98.7%, respectively. Among the 181 non‐CKD patients, the rates were 77.3% (140/181), 98.9% (179/181), and 98.9% (179/181), respectively. Among the 54 CKD patients, the rates were 83.3% (45/54), 98.1% (53/54), and 98.1% (53/54), respectively. There were no significant differences in the virologic response rates between the two groups ( P = 0.449 for RVR, 0.545 for ETR, and 0.545 for SVR). In the CKD group, the eGFR level did not significantly change throughout the treatment period. There was no significant difference in the incidence of TEAEs or treatment discontinuation due to TEAEs between the two groups. Conclusion: The present study showed that the effects and safety of OBV/PTV/r therapy in genotype 1b chronic hepatitis C patients with non‐dialysis CKD were not inferior to those in patients without CKD.